PTH-094 Providing a small bowel endoscopy service: the fall and rise of enteroscopy?. (23rd September 2015) - Sidhu, R; McAlindon, M E; Imran, M; Drew, K; Hardcastle, S; Sanders, D S
Abstract : Introduction: There are few centres in the UK which currently offer a one stop service with capsule endoscopy, double balloon and push enteroscopy. There are no published data on the comparisons between the three modalities in the UK. We evaluated the impact of the small bowel service on diagnostic yield and patient management. We also investigated the demand for each modality on the provision of the service. Methods: Data were collected on patients that underwent push enteroscopy (PE, since January 2002), capsule endoscopy (CE, since June 2002) and double balloon enteroscopy (DBE, inception of service, July 2006). Data were collected on demographics, indication of referral and diagnosis obtained including subsequent follow-up/outcomes. The modality of investigation performed depended on the referral indication and the location of the suspected pathology. However the majority of patients had CE first followed by enteroscopy (either PE or DBE). The demand and diagnostic yield for each modality and impact on patient management was also assessed over the same time period. Results: 1246 CE's, 247 PE's and 102 DBE's were performed over 93 months. Forty per cent of the referrals originated from outside the region. The overall diagnostic yield was 34% for CE, 39% for PE and 43% for DBE, respectively (p=0.15). The diagnostic yield was highest for the indication of obscure gastrointestinal bleeding (OGB) for both PE (p<0.001) and CE (p<0.001). In patients who underwent CE for OGB, the most common finding was angioectasia in 24% of patients while small bowel tumours accounted for 3.2% of patients (n=19) and commoner in those ≤60 years of age (p=0.01). Management was altered in 24% of patients that underwent CE, 20% that underwent PE and in 33% of patients that underwent DBE. For all 3 modalities, this was in the form of referral for surgery, initiation or step up of inflammatory bowel disease directed therapy and biopsy or application of thermocoagulation/haemostasis techniques to lesions seen at enteroscopy. The increasing demand for CE has resulted in a relative decline in the number of PEs performed (p<0.001) while the demand for DBE is rising particularly for lesions considered beyond the reach of PE. In 2008, for every 24 CE's performed, one patient underwent DBE locally. Conclusion: All three modalities are complementary to one another. The use of CE first line followed by PE/DBE as an adjuvant to CE for either obtaining histology or therapeutic intervention ensures efficient use of the small bowel service. With the rise in the number of centres providing a CE service, the demand for DBE is also expected to increase. Hence, there should also be a provision to meet this rising demand at a national level.